2022
DOI: 10.3389/fimmu.2022.855978
|View full text |Cite
|
Sign up to set email alerts
|

Mini-Review: Can the Metastatic Cascade Be Inhibited by Targeting CD147/EMMPRIN to Prevent Tumor Recurrence?

Abstract: Solid tumors metastasize very early in their development, and once the metastatic cell is lodged in a remote organ, it can proliferate to generate a metastatic lesion or remain dormant for long periods. Dormant cells represent a real risk for future tumor recurrence, but because they are typically undetectable and insensitive to current modalities of treatment, it is difficult to treat them in time. We describe the metastatic cascade, which is the process that allows tumor cells to detach from the primary tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 164 publications
(175 reference statements)
0
9
0
Order By: Relevance
“…During in‐depth studies of the tumor microenvironment, TAMs are described as closely related to the occurrence and development of tumors 19,20 . Meanwhile, the infiltration of TAMs is also related to chemokines, such as TGF‐β, IL‐4, IL‐8, and CSF1 21,22 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…During in‐depth studies of the tumor microenvironment, TAMs are described as closely related to the occurrence and development of tumors 19,20 . Meanwhile, the infiltration of TAMs is also related to chemokines, such as TGF‐β, IL‐4, IL‐8, and CSF1 21,22 .…”
Section: Resultsmentioning
confidence: 99%
“…During in-depth studies of the tumor microenvironment, TAMs are described as closely related to the occurrence and development of tumors. 19,20 Meanwhile, the infiltration of TAMs is also related to chemokines, such as TGFβ, IL-4, IL-8, and CSF1. 21,22 Based on these theories, we explored whether DHX9 promoted glioma progression and infiltration of TAMs via regulating the expression of chemokines.…”
Section: Csf1 Is Involved In Dhx9-mediated Malignant Phenotypes and I...mentioning
confidence: 99%
“…Therefore, this hypoxic microenvironment can be capitalized to develop liver cancer‐selective targeted therapies. CD147 is a hub Ag that binds to other proteins (Intergrin, Hyaluronan, CD44, P‐gp/ABCB1, ABCG2, MCT‐1/4, CypA/B, and Gasdermin D) to drive the malignancy of cancer cells 2,3,5,14,26–28,34 . Previous studies revealed that hypoxia induces the upregulation of CD147 in liver cancer cells 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Cluster of differentiation 147 (CD147) is a highly expressed TAMA that promotes the malignancy of liver cancer through multiple mechanisms. CD147 stimulates the production of matrix metalloproteinases (MMPs) in stromal fibroblasts, endothelial cells, and cancer cells 2,3 . These characteristics make CD147 a new target for Ab targeting.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation